PERBUDAKAN DAN BURUH MIGRAN DI TIMUR TENGAH - Abdul Fadhil (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
Slavery is a state in which a person possesses or takes control over someone else. Some historians state that it began to emerge ensuing agricultural expansion, approximately ten thousand years ago. It grew along the development of trade and industry. In fact, the increase of trade and industry has stimulated the demand for labor to multiply the products for export. Therefore, more labors both local and migrant areneeded. Migrant labor is one migrating from one’s birth place to another location and then works and stays in a new place in a certain period of time. Hence, the difference in culture and perception between the labor and the employer may lead to intricating problems. This is what has happened to Indonesian labor who works in another country. This paper attempts to examine the core problem between labor issue and migrant labor, specifically in the Middle East.Keywords: slavery, migrant workers, migrant workers